Professional sports in the dimension of socio-economic development of the regions of Ukraine - Leleka, V. (НТУ ДП, 2024)
Actual problems of the impact of globalization processes and European integration on the development of public administration in Ukraine and other countries are highlighted in the works of V. Bashtannyk, R. Voytovych, I. Kravchuk, O. Orzhel, L. Prokopenko, O. Rudenko, O. Rudyka, N. Rudyk and many other Ukrainian scientists who made a significant contribution to the scientific and practical support of the reform of the domestic public administration system in accordance with European and international standards.
Keywords: professional sports; socio-economic development